2015
DOI: 10.1177/2158244015602752
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Scientists on Climate Change and Vaccines

Abstract: On climate change and other topics, conservatives have taken positions at odds with a strong scientific consensus. Claims that this indicates a broad conservative distrust of science have been countered by assertions that while conservatives might oppose the scientific consensus on climate change or evolution, liberals oppose scientists on some other domains such as vaccines. Evidence for disproportionately liberal bias against science on vaccines has been largely anecdotal, however. Here, we test this proposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
168
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(211 citation statements)
references
References 59 publications
15
168
1
5
Order By: Relevance
“…For example, in a recent study, liberals reported greater trust in scientists as sources of information regarding vaccines and climate change, and this partisan gap widened with education (19). Another recent study found that conservatives with greater Significance Public opinion toward some science and technology issues is polarized along religious and political lines.…”
mentioning
confidence: 99%
“…For example, in a recent study, liberals reported greater trust in scientists as sources of information regarding vaccines and climate change, and this partisan gap widened with education (19). Another recent study found that conservatives with greater Significance Public opinion toward some science and technology issues is polarized along religious and political lines.…”
mentioning
confidence: 99%
“…The polarization along partisan lines is not limited to climate science. For example, Hamilton, Hartter, and Saito (2015) showed that trust in scientists regarding vaccinations was also greater among Democrats than Republicans, and this polarization again increased with increasing education. The conservative-liberal split is particularly amplified in attitudes toward vaccinations against sexually transmitted diseases such as the human-papillomavirus (HPV), which is responsible for cervical cancer (Kahan, Braman, Cohen, Gastil, & Slovic, 2010).…”
mentioning
confidence: 99%
“…Lack of public trust in science illustrates these issues regarding the prior distributions. Despite scientific evidence on issues such as safety of childhood vaccines, safety of genetically modified foods and effectiveness of sexual health education these topics remain controversial . Although individual psychology may predispose individuals to embracing controversy, access to “prior distributions” is an important determinant .…”
Section: Discussionmentioning
confidence: 99%